Role of testosterone: cortisol ratio in age- and sex-specific cortico-hippocampal development and cognitive performance. (31st March 2021) - Caccese, Christina; Jones, Sherri Lee; Ramesh, Mrinalini; Yu, Ally; Brossard-Racine, Marie; Nguyen, Tuong-Vi
Abstract: Testosterone (T) and cortisol (C) are steroid hormones that have been argued to play opposing roles in shaping physical and behavioral development in humans. While there is evidence linking T and C to different memory processes during adulthood, it remains unclear how the relative levels of T and C (TC ratio) may influence brain and behavioral development, whether they are influenced by sex of the child, and whether or not they occur as a result of stable changes in brain structure ( organizational changes), as opposed to transient changes in brain function ( activational changes). As such, we tested for associations among TC ratio, cortico-hippocampal structure, and standardized tests of executive, verbal, and visuo-spatial function in a longitudinal sample of typically developing 4–22-year-old children and adolescents. We found greater TC ratios to be associated with greater coordinated growth (i.e. covariance) between the hippocampus and cortical thickness in several areas primarily devoted to visual function. In addition, there was an age-related association between TC ratio and parieto-hippocampal covariance, as well as a sex-specific association between TC ratio and prefrontal-hippocampal covariance. Differences in brain structure related to TC ratio were in turn associated with lower verbal/executive function, as well as greater attention in tests of visuo-spatial abilities. These results support the notion that TC ratio may shift the balance between top-down (cortex to hippocampus) and bottom-up (hippocampus to cortex) processes, impairing more complex, cortical-based tasks and optimizing visuospatial tasks relying primarily on the hippocampus.